2014
DOI: 10.1002/jrs.4612
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polycyclic aromatic hydrocarbons using Raman and surface‐enhanced Raman spectroscopy

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous atmospheric pollutants and food contaminants, which exhibit potent carcinogenicity, mutagenicity, and teratogenicity. Vibrational spectroscopy techniques, especially Raman spectroscopy and surfaceenhanced Raman spectroscopy (SERS), can be potentially used as an alternative technique to liquid and gas chromatography in PAH analysis. However, there is limited information on the intrinsic Raman and SERS fingerprints of PAHs. In this study, we have acquired th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…6(a)). In this study, the area of the Raman laser spot was 0.0143 mm 2 [27], and the surface area for a single Fe 3 O 4 hemisphere is estimated to be~0.0006 mm 2 Fig. 6(a)).…”
Section: Sers Enhancementmentioning
confidence: 80%
See 2 more Smart Citations
“…6(a)). In this study, the area of the Raman laser spot was 0.0143 mm 2 [27], and the surface area for a single Fe 3 O 4 hemisphere is estimated to be~0.0006 mm 2 Fig. 6(a)).…”
Section: Sers Enhancementmentioning
confidence: 80%
“…The intense Raman peaks in the range 1200e1600 cm À1 were mainly recognized as the CeH bending modes. Peaks appearing at 300-1000 cm À1 with lower intensities are mainly attributed to the CeC bending modes coupling with the CeH bending modes [27]. It should be noted that the vibrational mode assignments only convey the most dominant oscillations, whereas in most cases, the predicted peaks are a result of the combined vibrations of multiple atoms and bonds within the molecule.…”
Section: Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…They identified characteristic Raman and SERS peaks for five PAH compounds and the limits of detection were established. Such information could be useful for developing SERS assays for simple and rapid PAH identification . Firkala and co‐workers have used SERS to study the behavior of substituted propenoic acids used in heterogeneous catalytic asymmetric hydrogenation.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Advantages of UV resonant Raman spectroscopy (UVRRS) were first demonstrated by Asher and Johnson in their study of PAHs. Characterization of PAH by Raman spectroscopy is a challenge with classical methods in the visible range and further more at high pressure. Recent X‐ray diffraction studies on PAHs, pyrene, and phenanthrene have shown that phase transitions occur at pressures under 2GPa.…”
Section: Introductionmentioning
confidence: 99%